A Robot Platform for Highly Efficient Pollutant Purification - Wang, Haocheng; Yu, Shimin; Liao, Junjie; Qing, Xudong; Sun, Daxing; Ji, Fengtong; Song, Wenping; Wang, Lin; Li, Tianlong (Frontiers in Bioengineering and Biotechnology, 2022)
We describe a new highly efficient robot platform for pollutants adsorption. This robot system consists of a flapping wing micro air vehicle (FWMAV) for long-distance transportation and accurately delivery and a cost-effective multifunctional Janus microrobots for pollutants purification. The FWMAV fly like a bat or a bird. The Janus microrobot, that composed of silica microsphere, nickel layer and hydrophobic layer, was used to recover the oil and organic pollutant. These Janus microrobots were capable of a powerful propulsion up to 9.6 body lengths per second, along with on-demand speed regulation and remote navigation. These Janus microrobots can continuously carry oil droplets in the aqueous environments under the control of uniform rotating magnetic field. Due to the fluid dynamics induced by the Janus microrobots, a highly efficient removal to the Rhodamine B is obtained. This smart robot system can open the door for accurately pollutants purification.